Discipline, grievance & dismissal - Morris, Sue (1993)
All managers at some point face the prospect of handling discipline or grievance procedures. Managed well, the outcome can lead to increased performance, a clearer understanding of required standards and, in the case of grievance, a balanced and unequivocal statement of fair play for all employees. Even where dimissal is involved, adherence to correct procedures will minimise the difficulties and help avoid potential legal involvement. [This book] is a simple comprehensive guide aimed at helping managers at all levels.